Analysis Principles of Personal Data Protection on COVID-19 Digital Contact Tracing Application: PeduliLindungi Case Study - Pratama, Anugrah Muhtarom; Pati, Umi Khaerah (Lex Scientia Law Review, 2021)
This article aims to review the application of the principle of personal data protection as part of privacy rights in the PeduliLindungi application considering that on the one hand, the PeduliLindungi application helps the government to reduce the spread of the COVID-19 virus. But on the other hand, there is a threat of misuse of personal data in the future. This background article is based on the use of the PeduliLindungi application, which was initially used to track the spread of the virus during the COVID-19 pandemic. But it seems that the public will increasingly use its use in the future, especially now that it has begun to be planned as an e-wallet and started integrating with several other applications. This article reveals that there has been a dual role by the Ministry of Communication and Informatics as a supervisor and controller of personal data in Indonesia so that it has implications for the PeduliLindungi application that has not fully applied the principles of personal data protection when collecting, processing, and storing personal data. For the future, a comprehensive legal development drive is needed related to the protection of personal data. There is a personal data protection agency and Data Protection Officer (DPO) to more strongly enforce the principles of personal data protection.